2007
DOI: 10.1016/j.jneb.2006.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Web-based Food Portion Training Program on Food Portion Estimation

Abstract: Objective-Assess the effects of a prototype computerized food portion tutorial (CFPT).Design-Participants were randomly assigned to estimate portion sizes for selected foods either prior to or following CFPT training (between group), and those estimating before CFPT training reestimated portions after training (within group). Setting-Research offices.Participants-Seventy-six adult participants without dietary restrictions. Intervention-The CFPT is a web-based food portion training that displays varied portions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…A follow-up study conducted 3 months after initial training about SS showed that the immediate positive impact had not been maintained (96) . Some studies showed that SS guidance had no impact (70,(98)(99)(100)(101) and others resulted in under-or overestimation of SS (negative impact) (102,103) . These equivocal results cannot be explained by the different methods of communicating SS information, e.g.…”
Section: Consumer Understandingmentioning
confidence: 99%
“…A follow-up study conducted 3 months after initial training about SS showed that the immediate positive impact had not been maintained (96) . Some studies showed that SS guidance had no impact (70,(98)(99)(100)(101) and others resulted in under-or overestimation of SS (negative impact) (102,103) . These equivocal results cannot be explained by the different methods of communicating SS information, e.g.…”
Section: Consumer Understandingmentioning
confidence: 99%
“…One assesses habitual beverage intake (BEVQ-15) [18], and the other measures usual physical activity level, Stanford Leisure-Time Activity Categorical Item 2.2 (L-Cat) [19]. There are several computerized nutrition education delivery [7,20,21] and dietary assessment tools [8,13,22-28] and a few Web-based physical activity questionnaires [12,29,30] currently available; however, to the best of our knowledge, no computer-based beverage intake questionnaire exists. The recently developed Automated Self-Administered 24-hour Recall [31] is computer-based and does contain questions about beverage intake; however, results on its validity and usability have yet to be published [32].…”
Section: Introductionmentioning
confidence: 99%
“…Training shifted accuracy from under-to overestimation (Riley et al, 2007). To date, therefore, the combination of caloric education and feedback training, albeit for portion size estimation, appears to have little to no effect on portion-size estimation.…”
Section: Calorie Estimation Training Programsmentioning
confidence: 94%
“…As expected, exposure to training and feedback improved portionsize accuracy; however, training effects did not generalize to new foods one month later (Rapp, Dubbert, Buttross, & Burkett, 1988). Riley et al(2007) extended this work by creating a web-based training that allows the participant to control the angle(s) at which each portion is viewed and provides feedback on accuracy. Participants either received this training immediately or after estimating the portion size of their own self-served meal.…”
Section: Calorie Estimation Training Programsmentioning
confidence: 99%